Textsortenbedingter Aspekt-Tempus-Gebrauch im Russischen - Appel, Daniela (Specimina philologiae Slavicae, 1996)
In the work presented here, (...) the real weight, the frequency of use of the temporal functions, which are inseparable from the temporal functions, are the center of interest in certain environments. In the core parts of the work on journalistic, everyday language and dramatic, narrative, administrative and scientific types of text essential questions for the representation of the aspect-tense functions are answered. New problems, which arise only from the question and have not been addressed in the literature, will be followed, especially the expectability of certain forms and functions in the course of the text.